Highly Flexible Infrared Emitter with Spatially Controlled Emissivity for Optical Security. Issue 4 (18th January 2023) - Kang, Dongkyun; Kim, Yeongseon; Kim, Chanhee; Lee, Myeongkyu
Abstract: Engineering the infrared (IR) emissivity of a material or structure is crucial for a variety of fields, including thermal camouflage, radiative cooling, personal thermal management, and optical security. For practical and wide‐spread use, the emitter should possess high mechanical flexibility while maintaining the capabilities of space‐selectively and dynamically controlling its emissivity. In this paper, an optical resonator consisting of a Ge2 Sb2 Te5 (GST) layer on top of a thin metal reflector stationed on a flexible substrate is presented as an IR emitter that satisfies the aforementioned requirements. A laser‐induced phase change from amorphous to crystalline GST enables dynamic tuning of the local emissivity of the resonator. This study illustrates that although GST is a brittle material, the emitters fabricated on plastic and paper substrates are highly robust against bending up to a radius of curvature of 0.5 cm. Moreover, visible light and IR images can be independently recorded in the same region by employing a spatially modulated laser beam owing to the multispectral properties of GST. The fact that a single emitter can exhibit different visible and IR images is particularly attractive for optical security applications, including anti‐forgery. This feature is experimentally demonstrated using white paper and color‐printed paper. Abstract : A Ge2 Sb2 Te5 (GST) based infrared emitter is fabricated on a flexible substrate such as plastic and paper, and its emissivity is space‐selectively controlled using a spatially modulated pulsed laser beam. The multispectral properties of GST enable different visible and thermal images to be simultaneously printed in the same area of the emitter. This provides a promising feature for optical security, including anti‐forgery.